Engineered Cell-Based Therapeutics: Synthetic Biology Meets Immunology - Caliendo, Fabio; Dukhinova, Marina; Siciliano, Velia (Frontiers in Bioengineering and Biotechnology, 2019)
Synthetic Biology has enabled new approaches to several medical applications including the development of immunotherapies based on bioengineered cells, and most notably the engineering of T-cells with tumor-targeting receptors, the Chimeric Antigen Receptor (CAR)-T cells. CAR-T-cells have successfully treated blood tumors such as large B-cell lymphoma and promise a new scenario of therapeutic interventions also for solid tumors. Learning the lesson from CAR-T cells, we can foster the reprogramming of T lymphocytes with enhanced survival and functional activity in depressing tumor microenvironment, or to challenge diseases such as infections, autoimmune and chronic inflammatory disorders. This review will focus on the most updated bioengineering approaches to increase control, and safety of T-cell activity and to immunomodulate the extracellular microenvironment to augment immune responses. We will also discuss on applications beyond cancer treatment with implications towards the understanding and cure of a broader range of diseases by means of mammalian cells engineering.